Histological Examination of Cholecystectomy Specimens - Saqib Ur Rehman, Awais Ali Khan , Babar Shamim, Rehan Saleem , Maria Shahzadi ,Zaeem Ali Khan (Journal of Rawalpindi Medical College, 2014)
Background: To determine whether routine histological examination of cholecystectomy specimens is an obligation or an option. Methods: In this descriptive study patients undergoing cholecystectomy either by open or laparoscopic technique were included. Patients with pre-operative diagnosis of malignancy, mass gallbladder on ultrasound/CT scan, metastatic gallbladder disease, and gross malignancy of gallbladder or local invasion from other viscera found during surgery and autolysed specimens were excluded from the study. The American Joint Committee on Cancer (AJCC) Tumour Nodal Metastasis (TNM) system was the reference for staging carcinoma gallbladder.9 Results: Gallbladder adenocarcinoma was detected in 0.21% cases, out of 940, on histological examination. Mean age of occurrence was 68.5 years. Both patients had polyps on pre-operative ultrasonography and per-operatively. One patient also had associated gallstones. None of the macroscopically normal looking specimens had malignancy. Conclusion: Frequency of incidental carcinoma gallbladder in specimens of cholecystectomy is very low.